Exploring the impact of discovery learning and self-efficacy on students’ mathematical reasoning skills - Sylvia Rabbani; Ryan Dwi Puspita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The research aims to test the effect of discovery learning on mathematical reasoning and analyse the differences in impact based on elementary school students' self-efficacy level. This study uses a quantitative approach with a quasi-experimental pre-test-post-test control group type design. The research sample consisted of 120 elementary school students randomly divided into experimental and control groups. The experimental group was given treatment for eight meetings using the Discovery Learning model, while the control group followed normal learning. The instruments used included a mathematical reasoning test and a self-efficacy questionnaire. Data analysis was carried out using paired sample t-test and independent sample t-test to determine the effect of the learning model, as well as one-way ANOVA to analyse differences in influence based on the level of self-efficacy. The results showed that the Discovery Learning model significantly improved students' mathematical reasoning skills with a value of <0.001. In addition, there was a significant difference in the acquisition of mathematical reasoning skills based on students' self-efficacy level. These findings indicate the importance of considering academic self-confidence factors in designing effective mathematics learning in elementary schools